Development and research of a portable distance measuring device - Salivonyk, Nataliya; Khrystyuk, Andriy; Zhabchyk, Victoria (Моделювання, керування та інформаційні технології, 2019)
The basic steps of developing a microprocessor ultrasonic device for measuring the distance to the object are shown. The structure of the device proposed. Results of the research of work of the developed device for the possibility of its use are presented and analyzed.